First successful case of chemical pleurodesis with oxytetracycline through Rocket® Pleural Vent™: ambulatory pneumothorax device for pneumothorax. Issue 7 (7th August 2019) - Kwok, Wang Chun; Cheng, Ka Chun; Lam, David Chi Leung; Tam, Terence Chi Chun
Abstract : A 79‐year‐old woman with asthma and idiopathic pulmonary fibrosis was admitted for a first episode right apical secondary spontaneous pneumothorax. Due to a lack of pleural separation inside the safety triangle, Rocket® Pleural Vent™ was inserted in the second intercostal space, mid‐clavicular line, as guided by thoracic ultrasound. Although the lung fully re‐expanded the next day, there was persistent air leak and so chemical pleurodesis with oxytetracycline was performed with success. There was no recurrence of pneumothorax and the patient was discharged two days afterwards, and a follow‐up X‐ray taken eight months later did not reveal any recurrence of the right‐sided pneumothorax. This is the first reported case of successful chemical pleurodesis through Rocket® Pleural Vent™ for pneumothorax, which may serve to provide additional alternatives to the management of secondary spontaneous pneumothorax that is indicated for pleurodesis after lung re‐expansion. Abstract : This is the first reported case of successful chemical pleurodesis through Rocket® Pleural Vent™ for pneumothorax, which may serve to provide additional alternatives to the management of secondary spontaneous pneumothorax that is indicated for pleurodesis after lung re‐expansion.